Persepsi masyarakat terhadap peran ganda pada perempuan sebagai wanita karier dalam membantu ekonomi keluarga - Astuti, Ayu Widya; Sapitri, Dea Nur; Jannah, Althariqul; Triana, Puput; Harahap, Rizki Ikhwana; Erni, Sukma (Journals of Indonesian Multidisciplinary Research, 2024)
This study aims to determine the dual role of women as career women in helping the family economy through a home kiosk business in Pekanbaru, Riau. This research was conducted using a qualitative approach. The results of this study show that economic motivation is the reason for women to perform multiple roles in moderate categories. The results also showed that in terms of perception and action of multiple role strategies, the majority of women want a balance between the two (the priorities of family and business). The last result, family welfare, objectively falls into the welfare category, and subjectively falls into the medium welfare category.